ENFORCEMENT AND PRACTICE OF LABOUR STANDARDS IN SPECIAL ECONOMIC ZONES: A PRELIMINARY INQUIRY AT COCHIN SPECIAL ECONOMIC ZONE - ANUPA JACOB AND MARTIN PATRICK (AJRBEM: ASIAN JOURNAL OF RESEARCH IN BUSINESS ECONOMICS AND MANAGEMENT, 2012)
In the post liberalisation era, with the objective of becoming export-friendly, India expanded the scale of operation of its export ventures by establishing Special Economic Zones. In order to enhance export competitiveness in the international market, the units in the zones resorted to cost cutting devices. The burden of this was borne by the labourers in the form of lower wages, violation of workers’ rights, compulsory overtime, job insecurity, poor working conditions, use of pressure tactics to meet deadlines, etc. In this context, the study analysed the working conditions in Cochin special Economic Zone situated in a highly organised society like Kerala. To evaluate working conditions among skilled workforce, data was collected from capital intensive electronics sector. Data from labour intensive food processing and textile sectors were collected to assess the working conditions among relatively less- skilled workers especially women. Suitable diagrams and simple statistical tools were used to analyse the data. The results confirmed that labour standards were not properly observed in all the three units, though the electronics sector was comparatively better off in protecting workers interests. The units in the zone preferred to employ young workers, who are mostly females and also unskilled, who could work hard for the firm. Wage discrimination on the basis of gender, skill acquired and nature of employment existed. However, they received social security benefits and allowances like PF, Gratuity etc. The working environment, attitude and approachability of the management were also reported to be satisfactory. The study also proved that enrollment in trade union was a necessity for the proper provision of working conditions by the management.